Wearing-off Identification in Parkinson's Disease: The shapd-woq Study - Wan, Ying; Yuan, Canxing; Hou, Xiaojun; Chen, Wei; Wang, ChunYan; Gao, Shan; Wang, Yuhui; Jin, Lingjing; Liu, Zhenguo (Frontiers in Neurology, 2020)
Objectives: to clarify the frequency of wearing-off phenomenon (WO) and the validity of Chinese version 9-item of wearing-off questionnaire (CWOQ-9) in WO identification in this large population Methods: Parkinson’ patients treated with antiparkinsonian medications were consecutively recruited into this observational, cross-sectional investigation. Patients completed the CWOQ-9 prior to the independent clinician assessment. Results: 1385 patients were included into the analysis. The mean age was 69.7± 9.5 years old and the mean disease duration was 5.8±4.7 years. Clinicians identified WO in 763 patients, with the overall prevalence of 55.1%. In patients within 1 year of disease duration, clinicians diagnosed WO in 8 patients, with the percentage of 12.9%. With the disease progression, the WO frequency gradually increased to 76.2% in patients with 10 to 15 years of disease duration. Then it slowly decreased at a longer disease duration. The occurrence of WO was closely associated with the disease duration, H&Y staging and levodopa daily dose. CWOQ-9 identified 1071 patients (1071/1398, 77.33%) that had WO related symptoms. The mean CWOQ-9 score was (3.4±1.6). CWOQ-9 corresponded with clinician assessments of WO in 734 of 763 cases; clinicians disagreed with the CWOQ-9 considering the presence of WO in 337 of 1071 cases. The sensitivity and specificity of CWOQ-9 was 96.2% and 45.8%, respectively. Conclusions: WO occurred frequently at the early and middle stage of PD. CWOQ-9 was qualified as a pre-visiting screening tool for clinicians to better identify WO